2021
DOI: 10.1039/d0sc03715j
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular strategies in artificial photosynthesis

Abstract: This review describes supramolecular strategies for optimization and integration of components needed for the fundamentals of artificial photosynthesis: light harvesting, charge-separation and catalysis, which are relevant for solar-to-fuel devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 143 publications
(167 reference statements)
0
83
0
Order By: Relevance
“…[1][2][3][4][5] Natural photosynthetic systems contain LH antennae that absorb in the complementary regions of the solar spectrum ultimately leading to panchromatic absorption. 6,7 Efficient harvesting of sunlight can be achieved by using biomimetic architectures, 8 with intense and panchromatic absorption in the red-green-blue (RGB) region. Such architectures can be constructed by carefully choosing chromophores absorbing in these three regions of the solar spectrum that show ultrafast intrachromophoric energy transfer and are photochemically robust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Natural photosynthetic systems contain LH antennae that absorb in the complementary regions of the solar spectrum ultimately leading to panchromatic absorption. 6,7 Efficient harvesting of sunlight can be achieved by using biomimetic architectures, 8 with intense and panchromatic absorption in the red-green-blue (RGB) region. Such architectures can be constructed by carefully choosing chromophores absorbing in these three regions of the solar spectrum that show ultrafast intrachromophoric energy transfer and are photochemically robust.…”
Section: Introductionmentioning
confidence: 99%
“…Such architectures can be constructed by carefully choosing chromophores absorbing in these three regions of the solar spectrum that show ultrafast intrachromophoric energy transfer and are photochemically robust. 8 Multiple reports of articial LH arrays constructed either through covalent bonds 2,9 such as dendrimers, [10][11][12][13] conjugated polymers, 14 multichromophoric arrays 8,9,15,16 or non-covalent achitectures 8,[17][18][19][20] are available. However, the majority of the reported covalent multichromophoric LH systems are based on the one step Förster resonance energy transfer (FRET) process between the energy donor and energy acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…Proton permeability was performed using a Teflon set-up that comprised two compartments, the feed and stripping solutions, separated by the tested membrane. Samples for these measurements were placed between two compartments giving a total membrane area equal to 0.66 cm 2 . The solution volume in each compartment was 200 mL.…”
Section: Membrane Preparation and Characterizationsmentioning
confidence: 99%
“…During the last decades, the interest in finding more sustainable and respectful methods for generating energy such as artificial photosynthesis and electrochemical energy storage systems has greatly attracted the interest of the scientific community [1][2][3][4][5]. Protonconducting membranes are one of the most important components in both energy systems taking into account their roles: separation of the two compartments and conduct selectively the protons from anode to cathode [6].…”
Section: Introductionmentioning
confidence: 99%
“…3 In the field of catalysis, supramolecular concepts have been developed to tune reactivity, selectivity as well as in-situ catalyst assembly, 4,5 highlighting the enormous potential of this field of research. Over the last decade, pioneering studies have demonstrated the potential of supramolecular catalysis for energy conversion and storage, 6,7 e.g. in the fields of water oxidation, 8,9 CO2 reduction, 10 and the hydrogen evolution reaction (HER).…”
Section: Introductionmentioning
confidence: 99%